2015
DOI: 10.1016/j.apnr.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Recognising female sexual dysfunction as an essential aspect of effective diabetes care

Abstract: The following literature review will focus on sexual dysfunction in women living with diabetes, drawing on international studies in this specialist field. The key aim of this paper is generate a greater understanding and recognition of the issues facing these women and to determine a more proactive approach to identification, consultation and potential treatment options. The main findings highlight the unique role practitioners have with women with diabetes and how to facilitate partnership working. Nurses hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Some observational studies have shown an association between poor glycemic control, expressed by elevated levels of glycated hemoglobin (HbA1c), and ED, whereas other studies did not report any association [9]. The different methodological approaches used in the different studies may explain, at least in part, these divergent results [10]. Moreover, diabetes is commonly associated with hypertension, hyperlipidemia, overweight and obesity, metabolic syndrome, smoking, sedentary lifestyles, and autonomic neuropathy, which are recognized as risk factors for ED.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some observational studies have shown an association between poor glycemic control, expressed by elevated levels of glycated hemoglobin (HbA1c), and ED, whereas other studies did not report any association [9]. The different methodological approaches used in the different studies may explain, at least in part, these divergent results [10]. Moreover, diabetes is commonly associated with hypertension, hyperlipidemia, overweight and obesity, metabolic syndrome, smoking, sedentary lifestyles, and autonomic neuropathy, which are recognized as risk factors for ED.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A woman and her partner can be referred to an experienced sexual relationship therapist, who uses techniques such as the Cognitive Behavioural Therapy and Sensate Focusing, helping couples to learn sensual tactile techniques, in order to try to decrease possible tension and improve performance, thus helping them to overcome the existing sexual problems [25]. These psychological approaches can be helpful, although cultural and religious preferences should be taken into account when suggesting them [26]. Other therapeutic options include the usage of vaginal lubricants, clitoral engorgement devices and various potentially useful medications (flibanserin, testosterone, bupropion, sildenafil etc.)…”
Section: Diagnostic and Treatment Approachesmentioning
confidence: 99%
“…Changes in structures within the genitourinary system due to vascular and neuropathic damage may lead to decreased hydration of the vaginal membrane causing dyspareunia and impede sexual response and arousal. 7,8 It has also been identified that psychological factors, diabetes medications and comorbidities may exacerbate SD in women with Type 1 diabetes. 9 Women affected by Type 1 diabetes are mainly young women who are relatively free of age-related complications, and therefore, SD could have a major impact on their quality of life with the reoccurrence of sexual disappointment and emotional discomfort.…”
mentioning
confidence: 99%